Impact of adjacent building on outdoor ventilation around a layout of two buildings - Adinoyi, Ayo Samuel (2014)
The outdoor air ventilation impact ofa taller building in different configurations of a layout of two adjacent buildings is presented in this paper. The critical parameters investigated are the separation distance (S) between the buildings and the ratio of height of downwind building to that of the building upwind, herein referred to as building height ratio (HR). The aim is to explore intermediate spacing distances which may engender acceptable ventilation around the buildings.A three-dimensional (3-D) numerical simulation employing the Computational Fluid Dynamics technique which adopts the Reynolds-Averaged Navier-Stokes equation and the realizable k-e turbulence model was used to study the turbulent flow field around the full-scale two-building configurations.Results show that velocity ratio generally increases with height ratio, indicating that more air motion is induced at the pedestrian level as the height of the downwind building increases. For each of the height ratios, there is a spacing distance at which the velocity ratio is highest. The spacing distances at which the maximum velocity ratio occurs for the various height ratios are proposed. The dimensionless air exchange rate generally increases with height ratio, indicating that greater quantity of air from within the cavity between the buildings is exchanged with air from outside the cavity, which should result in better air quality. The findings of the study demonstrate the importance of incorporating wind data of an urban area in formulating guidelines for layout of buildings in the area.